MODEL PENERAPAN ANGGARAN BERBASIS KINERJA DI RS TK. II. DR. R. HARDJANTO BALIKPAPAN - Arviana, Nerissa; Handayani, Nining; Rinawati, Rinawati; Andriani, Rian (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Performance-Based Budgeting (PBB) at Tk. II Hospital Dr. R. Hardjanto Balikpapan Performance-Based Budgeting (PBB) is an budgeting approach that links resource allocation with measurable performance outcomes, aiming to improve organizational efficiency, effectiveness, and accountability. This research aims to analyze how PBB is implemented at Tk. II Hospital Dr. R. Hardjanto Balikpapan (RST), identify challenges and opportunities, and determine the budgeting model applied to support the achievement of the hospital's strategic goals. This study uses a qualitative approach with a case study at RST. Data was collected through in-depth interviews with relevant parties and a review of documents related to budgeting and performance reports. The research findings indicate that the implementation of PBB at RST faces several challenges, including limited understanding of the PBB concept among staff, resistance to change, lack of an integrated performance measurement system, and sub-optimal management support. However, opportunities for improvement exist through increased socialization, continuous training, development of supporting information systems, and strengthened commitment from all relevant parties. The conclusion of this research is that PBB at RST is an evolutionary process carried out gradually. The understanding of PBB is still limited among leaders and staff, but it is practically underway. The budgeting model starts with a bottom-up budget planning process, remains fixed during the budget period, and evaluations are conducted periodically through internal and external audit systems.